Intakes of nutrients in Italian children with celiac disease and the role of commercially available gluten‐free products. Issue 5 (17th December 2012) - Zuccotti, G.; Fabiano, V.; Dilillo, D.; Picca, M.; Cravidi, C.; Brambilla, P.
Abstract Background Celiac disease (CD) is a chronic gluten‐sensitive enteropathy. Life‐long gluten‐free diet (GFD) is the only therapeutic option; however, it may contribute to the consumption of an unbalanced diet. The present study aimed to evaluate the dietary intake of CD affected children on a GFD and compare it with non‐celiac children and with Italian nutritional intakes recommendations, as well as evaluate the contribution of commercially available gluten‐free products (GFPs). Methods Eighteen celiac children, median age 7.6 years, median GFD duration 4.2 years, and 18 non‐celiac controls, were enrolled in a cross‐sectional age‐matched study. Dietary intakes of both groups were collected using a food frequency questionnaire and a 24‐hour dietary recall. Nutritional intakes were compared between the group and controls and with Italian dietary reference values. The contribution of GFPs to energy and macronutrient intakes was evaluated. Results Median energy intake was significantly higher in CD patients than in controls (8961.8 and 5761.0 kJ day−1; P < 0.001). CD subjects showed higher carbohydrate intakes and lower fat intakes compared to controls. Protein‐derived energy did not differ. By contrast to control subjects, energy derived from carbohydrate intakes in CD children met the Italian recommendations. Both children groups showed higher protein and fat intakes than recommended in Italy. GFPs consumption accounted for 36.3% of daily total energy intake. Conclusions Intakes of simple sugars, fats and protein exceeded the National recommendations for health. Children with CD had significantly higher energy intakes than controls, although body mass index was comparable across the groups. Lack of nutritional information for GFPs prevented complete dietary analysis of subfractions of fat and micronutrient intakes. This aspect need to be addressed if studies in this field are to be meaningful in the future.